The International Monetary Fund under constraint : legitimacy of its crisis management - Riesenhuber, Eva (Legal aspects of international organization, 2001)
"The International Monetary Fund under Constraint exposes a legal dilemma facing the IMF as it tackles international crisis management. Using the Asian crisis and more particularly economic and political events in Indonesia as an example, this volume examines whether the Fund's activities in Asia were legally justified." "The results of this analysis lead to the following question: What future role can the IMF play in the international financial architecture? The principles of international law and the legal foundations of the Fund are used to analyse the reform suggestions of economic experts and to find a suitable concept for future IMF involvement in financial crises and crises prevention." "This volume is a legal analysis of IMF activities. It presents the combination of law and economics which was originally at the heart of the IMF but which so far has been ignored in today's reform discussion."--BOOK JACKET.